Tinjauan Theory Planned Behavior Dalam Keputusan Memilih Program Studi Sarjana Kedokteran Gigi pada Perguruan Tinggi Di Kota Surabaya - Sabda Alam; Tri Kartika Pertiwi; Muhadjir Anwar (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – Data from the Indonesian Medical Council , as of April 24, 2024 there were 279,321 doctors registered in Indonesia. Of these, 220,664 people or 79% are general practitioners and specialist doctors, dentists and specialist dentists combined, the number reached 59,422 people, equivalent to 21% of the total doctors registered nationally. The urgency of this research is that the problem of lack of interest in the faculty of dentistry in Indonesia is a serious concern for many parties. Along with the times, the faculty of dentistry with little interest can hinder the progress of the dental health field.The analysis of interest in entering the undergraduate dental program is important to understand the factors that influence students in choosing the dental program, such as interest, talent, career interest, expectations, environment, and educational facilities Aim – The aim of this research is to analyze (1) the influence of gender stereotypes and family support on the decision to choose the dentistry study program, (2) the role of career prospects in moderating the influence of gender stereotypes and family support on the decision to choose the dentistry study program, Design / methodology / approach – The sample for this research consists of 143 students from the Faculty of Dentistry, class of 2023, at three universities with a Faculty of Dentistry: Universitas Airlangga, Universitas Hang Tuah, and Universitas Muhammadiyah Surabaya, who served as respondents. The sampling technique used is Probability Sampling, specifically Stratified Random Sampling. The data used is primary data collected through the distribution of questionnaires to respondents. The analysis was conducted using the Partial Least Square (PLS) method with Smart PLS version 4.0 softwaredescribe the methodology used in your research. Findings – The research results conclude that (1) gender stereotypes and family support can drive the decision to choose a dental medicine study program, (2) family support can drive the decision to choose a dental medicine study program, (3) career prospects strengthen the contribution of gender stereotypes to the decision to choose a dental medicine study program, but do not moderate the contribution of family support to the decision to choose a dental medicine study program Conclusion –. The profession of a dentist, which requires high precision to diagnose health problems, is often associated with certain gender expectations. The support that individuals receive can increase their confidence in making choices. There is a tendency to avoid jobs that are considered incompatible with existing gender norms, which then leads individuals to adjust their career choices. Parenting patterns that give freedom and trust to children, while still emphasizing responsibility for decisions made, are not directly influenced by career prospects. Research implication – The job of a dentist, which requires great precision to diagnose health problems, is often associated with gender-specific expectations. The support received by individuals can increase their confidence in making choices. There is a tendency to avoid occupations that are perceived to be incompatible with existing gender norms, leading individuals to adjust their career choices accordingly. Parenting that gives children freedom and trust, while emphasizing responsibility for decisions, is not directly influenced by career prospects. Limitations – These studies may have used relatively simple measures of gender stereotypes or based on generalized perceptions, which may not fully capture how more subtle or specific gender stereotypes affect individuals. For example, gender stereotypes are not just limited to whether a profession is suitable for men or women, but could involve expectations regarding the character traits or roles expected in that profession (e.g. whether women are perceived to be more empathetic in the health profession). Therefore, the use of more complex measurement tools for gender stereotypes could help provide a more accurate picture.